2022
DOI: 10.1021/acs.nanolett.2c01489
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Driven Mechanically and Tribologically Adaptive Hydrogels Solely Constituted of Graphene Oxide and Water

Abstract: Although mythologies and fictions have recorded living creatures fully composed of inorganics, it is however hard to turn inorganic constituents into lifelike materials in reality as they usually do not possess characteristics required for constructing a living organism. Here, we report to our knowledge the first biomimetic hydrogel in response to both pH and temperature variations that solely comprises graphene oxide and water. The hydrogel is capable of abruptly and reversibly switching its mechanical and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 37 publications
0
41
0
Order By: Relevance
“…Materials with convertible lubrication can allow an accurate manipulation of tribological interactions between two contacting moving parts, thereby being able to acquire a precise control over the efficiency, accuracy and reliability of large equipment or small devices. 8,[11][12][13][14][15] However, lubricants with two convertible friction states in which the CoF differs by more than one order of magnitude have seldom been reported. In this work, the DDACe microemulsion, which could abruptly and considerably switch its CoF by nearly 25 folds on the basis of a thermoreversible microemulsion-emulsion transition, was likely to have great potentials in intelligent devices and controllable transportation system that usually require dramatically switchable surface properties.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Materials with convertible lubrication can allow an accurate manipulation of tribological interactions between two contacting moving parts, thereby being able to acquire a precise control over the efficiency, accuracy and reliability of large equipment or small devices. 8,[11][12][13][14][15] However, lubricants with two convertible friction states in which the CoF differs by more than one order of magnitude have seldom been reported. In this work, the DDACe microemulsion, which could abruptly and considerably switch its CoF by nearly 25 folds on the basis of a thermoreversible microemulsion-emulsion transition, was likely to have great potentials in intelligent devices and controllable transportation system that usually require dramatically switchable surface properties.…”
Section: Discussionmentioning
confidence: 99%
“…As shown, the zeta potential of n-hexane droplets lowered from ~62 to ~17 mV along with a stepwise temperature increment from 20 to 50 ºC, corresponding to a strong attenuation of the thermodynamic stability that favours aggregation and coalescence of the oil droplets. 14,33 The temperature elevation also induced the interfacial tension of DDACe/EG mixture to increase by nearly 25 folds, which therefore strongly improved the interfacial energy of a n-hexane/water interface that hampers the formation of stable microemulsions. 20 By contrast, the interfacial tension of pure DDACe did not change prominently as a function of temperature, and the value was close to that of the surfactant/ glycol complex at 50 ºC.…”
Section: Thermoresponsive Behaviour Of the Ddace Microemulsionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the first biomimetic hydrogel that is responsive to both pH and temperature variations solely comprises graphene oxide and water . GO on its basal plane has abundant oxygen-containing groups in a honeycomb shape.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the first biomimetic hydrogel that is responsive to both pH and temperature variations solely comprises graphene oxide and water. 37 GO on its basal plane has abundant oxygen-containing groups in a honeycomb shape. In this study, we analyzed whether the treatment of GO/ radiation could affect the morphological changes of NPC C666-1 cells.…”
Section: Go Enhanced the Cell Apoptosis By Reducing Bcl-2 And Raising...mentioning
confidence: 99%